A comparison of artificial neural networks and bootstrap aggregating ensembles in a modern financial derivative pricing framework - Ryno Du Plooy; Pierre J. Venter (Journal of Risk and Financial Management, 2021)
In this paper, the pricing performances of two learning networks, namely an artificial neural network and a bootstrap aggregating ensemble network, were compared when pricing the Johannesburg Stock Exchange (JSE) Top 40 European call options in a modern option pricing framework using a constructed implied volatility surface. In addition to this, the numerical accuracy of the better performing network was compared to a Monte Carlo simulation in a separate numerical experiment. It was found that the bootstrap aggregating ensemble network outperformed the artificial neural network and produced price estimates within the error bounds of a Monte Carlo simulation when pricing derivatives in a multi-curve framework setting.
Keywords: 330; artificial neural networks; collateral; funding; multi-curve framework; vanilla option pricing